Traditional Chinese medicine for mild-to-moderate ulcerative colitis: Protocol for a network meta-analysis of randomized controlled trials. Issue 33 (August 2019) - Shen, Zhaofeng; Zhou, Qing; Ni, Yingjun; He, Weiming; Shen, Hong; Zhu, Lei
Abstract: Background: Ulcerative colitis (UC) is a universal chronic nonspecific intestinal inflammatory disease of unknown etiology. Although 5-aminosalicylic acid (5-ASA) is used as a first-line treatment for mild-to-moderate UC, some patients do not react well to it. Traditional Chinese medicine (TCM) plays a complementary role in the management of UC. A large number of randomized controlled trials (RCTs) have shown that TCM has a significant effect in the treatment of mild-to-moderate UC. However, due to the diversity of TCM treatments, its relative effectiveness and safety remains unclear. Therefore, we aim to compare the effectiveness and safety of TCM for mild-to-moderate UC by implementing a Bayesian network meta-analysis (NMA) and provide a reference for clinical treatment. Methods: According to the Cochrane Handbook, PubMed, MEDLINE, Embase, Web of Science, the Cochrane Library, CINAHL, China National Knowledge Infrastructure (CHKD-CNKI), Chinese Biomedical Literature database (CBM), and WANFANG database will be searched. Related randomized controlled trials (RCTs) that compared one TCM intervention with another or with 5-ASA (placebo) for mild-to-moderate UC from inceptions to February 2019 will be included. Two authors will screen the literature and extract data independently based on predesigned rules, and evaluate the risk of bias of included studies using the Cochrane Risk of Bias Tool. Both classical pair-wise meta-analysis and Bayesian NMA will be conducted using R-3.4.4 and WinBUGS-1.4.3 software. The ranking probabilities for all interventions will be estimated and the hierarchy of each intervention will be summarized as surface under the cumulative ranking curve. The consistency within network will be evaluated with Cochrane Q statistic and net-heat plot. The quality of evidence will be assessed by the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach. Results: The study results will be disseminated through a peer-reviewed journal publication or conference presentation. Conclusions: The findings will provide a systematic evidence-based medical evidence of TCM interventions in the treatment of UC and help clinical practitioners, UC patients, and policy-makers make more informed choices in the decision-making. Ethics and dissemination: Ethical approval and informed consent are not required since this is a protocol for a network meta-analysis based on published studies. The findings will be disseminated through a peer-reviewed journal publication or conference presentation. Registration: PROSPERO CRD42019133962.